2018
DOI: 10.1111/mve.12294
|View full text |Cite
|
Sign up to set email alerts
|

A distinct group of north European Aedes vexans as determined by mitochondrial and nuclear markers

Abstract: Abstract. The floodwater mosquito Aedes (Aedimorphus) vexans (Meigen, 1830) (Diptera: Culicidae) is common in several areas of Sweden and is predicted to become more abundant in the wake of expected changes in precipitation and temperature caused by climate change. As well as being a nuisance, Ae. vexans can act as a vector of over 30 viruses. In the event of an outbreak of disease caused by a vector-borne virus, knowledge of the distribution, population structure and intermixing of populations from different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Mosquitoes collected from Majorca (Ae. vexans A) would belong to the authors’ Group 2, which has also been reported in Hungary and Sweden (Lilja et al , 2018). Ae.…”
Section: Preliminary Evidence For Cryptic Speciationsupporting
confidence: 60%
See 1 more Smart Citation
“…Mosquitoes collected from Majorca (Ae. vexans A) would belong to the authors’ Group 2, which has also been reported in Hungary and Sweden (Lilja et al , 2018). Ae.…”
Section: Preliminary Evidence For Cryptic Speciationsupporting
confidence: 60%
“…The use of nuclear and mitochondrial markers has recently allowed the detection of two different lineages within Ae. vexans (Lilja et al , 2018). Our results are consistent with these findings, with all species delimitation analysis confirming the separation of at least two groups of Ae.…”
Section: Preliminary Evidence For Cryptic Speciationmentioning
confidence: 99%
“…Whole mosquitoes were used for the DNeasy Blood and Tissue Kit, while three legs from each specimen were taken for extracting DNA with the PrepMan ® Ultra Sample Preparation Reagent. DNeasy Blood and Tissue Kit was used in accordance with the manufacturers manual and the DNA extractions made with PrepMan ® Ultra Sample Preparation Reagent were conducted as specified in previous work [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…As noted above, the increased potential for reproducibility afforded by the use of established insect colony lines may also come at the expense of reflecting the epidemiologically relevant diversity present in field populations. Natural ‘populations’ may be highly genetically heterogeneous, and even represent an assemblage of multiple cryptic species [ 23 , 24 , 25 , 26 , 27 ]. This has been a particular problem for understanding the epidemiology of Culicoides -borne viruses in Northern Europe, where the females of some vector species are morphologically cryptic [ 28 ] (e.g.…”
Section: Source Of Vectorsmentioning
confidence: 99%